Multi-description multipath video streaming in wireless ad hoc networks - Xu, Yuanyuan. (2013)
In this paper, multiple description coding (MD coding or MDC) coupled with multipath transport is considered to provide robust video streaming in error-prone wireless ad hoc networks. Two problems are investigated for multi-description multipath (MDMP) video streaming in the unicast setting. The first one addresses multipath selection for balanced two-description coded video streaming. An interference-aware MDMP routing is formulated for single-radio networks by employing a time-division link scheduling method to eliminate interference, based on which an optimal path selection associated with the minimum reconstruction distortion of received video may be obtained with high complexity. A heuristic solution of low complexity is developed for the interference-aware multipath routing, by introducing a path metric taking into account intra-flow interference, inter-flow interference, link bandwidth and link “up” probability. The second problem touches on unbalanced-path based joint MD video coding and packet allocation for multiple paths of varying bandwidth and loss probabilities. An unbalanced-path based joint two-description video coding and description packet allocation utilizing redundant slices is proposed, which allocates slices in each description to two paths with varying bandwidth and optimally selects the amount of inserted redundancy according to different loss rates. Simulation results demonstrate the effectiveness of both the proposed MDMP routing scheme and the unbalanced-path based joint MD video coding and packet allocation approach in the wireless ad hoc networks.